Pandemic! 2 : chronicles of a time lost - Zizek, Slavoj (New York : Polity Press, 2021)
In this ... sequel to his acclaimed Pandemic!: COVID-19 Shakes the World, Zizek delves into some of the more surprising dimensions of lockdowns, quarantines, and social distancing--and the increasingly unruly opposition to them by 'response fatigued' publics around the world. Zizek examines the ripple effects on the food supply of harvest failures caused by labor shortages and the hyper-exploitation of the global class of care workers, without whose labor daily life would be impossible. Through such examples he pinpoints the inability of contemporary capitalism to safeguard effectively the public in times of crisis.
Introduction: why a philosopher should write about bringing in the harvest -- What we don't know, what we don't want to know, and what we can do -- The first of May in the viral world -- Covid-19, global warming, exploitation - the same struggle -- Why destroying monuments is not radical enough -- Father ... or worse -- Sex in the age of social distancing -- The (not so) brave new world of pigs and men -- A no-touch future? No, thanks! -- Where are Greta and Bernie? -- What movie is now playing out in real life? -- Deaths in paradise -- Now we live in a store of the worlds -- Yes, red pill ... but which one? -- Simple things that are hard to do -- (No time) to conclude: the will not to know.
Reprint. Originally published: New York : OR Books, 2020.
Keywords: COVID-19 (Disease) -- Economic aspects; COVID-19 (Disease) -- Social aspects; Epidemics -- Economic aspects; Epidemics -- Social aspects; Capitalism